Innovating from within: How does intrapreneurship influence the performance of public institution employees? - Luis Santos; Anderson R. Galvão; David Rodeiro-Pazos; Telma Mendes (Journal of Entrepreneurship and Public Policy, 2026)
Purpose This study aims to analyze how intrapreneurship influences commitment to work, employee satisfaction, innovative behaviour and employee performance in public organizations. Design/methodology/approach To develop this study, a structured questionnaire was applied to a sample of 503 employees from different Portuguese institutions. Data processing was performed using the structural equation modelling technique, using Smart PLS software. Findings The results show that intrapreneurship is positively associated with work engagement, employee satisfaction and innovative behaviour. Work engagement emerged as the strongest mechanism linking intrapreneurship to employee performance. Innovative behaviour showed a positive but marginal relationship with employee performance, suggesting that innovation-oriented behaviour may require organizational support to be translated into performance outcomes. Employee satisfaction, however, showed a negative relationship with performance, indicating that satisfaction alone may not be sufficient to improve employee outcomes in public institutions. Originality/value This study contributes to public sector intrapreneurship research by shifting attention from organizational-level innovation outcomes to employee-level attitudinal and behavioural mechanisms. It shows that work engagement, employee satisfaction and innovative behaviour should not be treated as interchangeable constructs and that the relationship between intrapreneurship and performance in public institutions is shaped by distinct mechanisms. The findings also contribute to entrepreneurship and public policy debates by highlighting the need for organizational and policy conditions that enable public employees to transform intrapreneurial initiative into innovation and performance.